دور أخلاقيات التسويق السياسي في كسب الرأي العام دراسة استطلاعية لآراء عينة من الناخبين في ٳقليم كوردستان/العراق - رشيد, ساكار عزيز; قرداغي, كاوە محمد فرج (Sulaimani Journal for Humanities, 2018)
The democratic countries and nations that believe in the devolution of power through fair elections attempt to show and introduce themselves, their candidates and political programmes in order to persuade people to elect them. For that reason, the principal aim of this study is to discover the role and effectiveness of ethical political marketing on receiving public opinion. The study has concluded that there is no ethics in the political marketing in Kurdistan Region, and candidates and political parties use all ways to collect the majority of votes and take power. Furthermore, they try to increase the votes by forgery and exchange the votes among candidates. This research introduces several recommendations and suggestions. The most significant one among these recommendations is that the candidates and political parties should obey and follow the instructions and moral values during election campaign in order to reconstruct voter's confidence and increase the turnout in election.
Keywords: Political marketing; Ethics; Public Opinion; Voting; Voters